Failure Mode and Effects Analysis With Analytical Hierarchy Process For Selecting The Best Design of VLM (Vertical Lift Module) Strategy - Lum, Chee Choong (2021)
A Vertical Lift Module (VLM) fits the needs for an effective and safe storage and retrieval system in a newly construct 5 storey manufacturing plant in Infineon Melaka. A VLM is able to recapture wasted floor space by utilizing all of unused vertical height, effective controlled pick and store rates for material, secure storage with user level access to protect materials and enhanced safety and ergonomics features such as shutter doors and optimum pick up heights for human operators. As there are many choices available in the market for VLMs and providing almost equivalent specifications. To overcome this limitation, a multi criteria decision analysis which involving the quality context, could be a helpful methodology, as Failure Mode and Effects Analysis (FMEA) has been widely used and accepted especially in semiconductor industry in various phases of the processes and product life cycle In this paper, a hybridized FMEA into a multi criteria decision making tool of Analytical Hierarchy Process is proposed, with AHP is used to provide a hierarchy based relationship between goal of the research, criteria, sub-criteria and alternatives. By incorporating FMEA as part of the AHP process, it shall strengthen the process of assigning weights for criteria. In this research, criteria such as cost, quality, delivery, service and financial are selected and the value of Risk Priority Number (RPN) from the FMEA is being utilized in the pair-wise comparison for sub-criteria of quality. Using subtraction method and follow by max-min normalization method to create the pair-wise comparison matrix representing sub-criteria of quality. While the remaining sub-criteria and between alternatives will proceed with standard AHP method in order to get the overall priority ranking. By employing FMEA, the priority matrix takes into account the weight of the critical factors in quality and simplified the complexity of assigning weights by decision makers. An actual application in the case study at Infineon’s selection for VLM is also presented to prove the applicability of the method in real industry setting. The result showed that the hybridized AHP-FMEA proposed similar outcome for the best alternative as compared to the Weighted Sum Model (WSM) that Infineon is currently practicing.